What the maps don't say. A look at geographical methods for the study of violence in the territory (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The phenomenon of violence, in some specific forms and modalities, requires a contextualized territorial study that can reveal the spatial distribution, the functioning, the relationships between the actors involved, being the State, parastatals and extrastatal actors. Starting from a critical review of geographical research methods, which include territorial analysis, context analysis and geospatial analysis, I discuss the relationships that weave the map of production and reproduction of patriarchal and mafia violence as a means and end of the exercise of political power in the territory. Maps are a political-aesthetic tool historically used to create the world and its relationships, rather than 'simply' representing it. In the official speech, the nation-state has built organized crime as a territorial competitor, a 'parallel' actor-association that challenges the monopoly of violence: a discourse that is geo-graphically converted, in the Mexican case, as a reworking of administrative units local with borders -polygons, in cartography- of the so-called cartels. What are the problems of this reading, of this point of view? How does geography, and the methodology that suggests, contribute to critically address the responsibilities of the narrative and material (re)production of violence? The (re)production the map of actors involved in violent phenomena?
Keywords: geographical methods, violence, organized crime, feminist theory, spatial analysis